Next-gen 5G antenna: antipodal vivaldi antenna using ferro A6s for enhanced performance at 60 GHz - Othman, Mohd Azlishah; Jaafar, Abd Shukur; Manap, Redzuan Abd; Misran, Mohamad Harris; Said, Maizatul Alice Meor; Suhaimi, Shadia; Hassan, Nurmala Irdawaty (2023)
The Antipodal Vivaldi Antenna (APVA) has been identified as a promising technology for use in 5G systems due to its high frequency, wide bandwidth, and high gain. In this study, we evaluated the performance of the APVA using Ferro A6s substrate at 60 GHz and compared it with other substrates. Our findings demonstrate that the Ferro A6s substrate exhibits superior performance in terms of return loss, gain, and bandwidth when compared with other substrates. Our research contributes to the field of high-frequency wireless communication and can pave the way for the development of better 5G systems. The results of this study have the potential to revolutionize 5G backbone communication.